Research on the correlation and potential mechanism of PKCδ expression with efficacy and prognosis in diffuse large B-cell lymphoma - Zhao, Xulu; Li, Shan; Zhu, Lin; Wu, Mei; Hu, Xin; Liang, Xiao; Wang, Shanshan; Maihemaiti, Aziguli; Adili, Abulikemujiang; Wen, Shujuan (Frontiers in Oncology, 2026)
IntroductionDiffuse large B-cell lymphoma (DLBCL) is the most common subtype of non-Hodgkin lymphoma. While the R-CHOP regimen achieves a 70% 5-year survival rate, patients with refractory or relapsed disease face poor prognoses. Therefore, it is very important to search for markers related to curative effect and prognosis, and to explore new targeted therapies. Protein kinase C delta (PKCδ), a serine/threonine kinase involved in cell proliferation, growth, and cancer progression, has been proposed as a prognostic marker in solid tumors, but its role in DLBCL remains underexplored. This study aimed to validate PKCδ as a prognostic biomarker and investigate its mechanistic contributions to therapeutic resistance.MethodsImmunohistochemistry (IHC) was used to analyze the expression of PKCδ in 200 DLBCL tissues to validate the correlation between PKCδ and therapeutic efficacy as well as prognosis. Using the DB and RIVA cell lines to stably knock down the PRKCD gene, we explored the role of PKCδ in cell proliferation, cell cycle, apoptosis, chemoresistance, and related signaling pathways through CCK-8 assays, flow cytometry, RNA sequencing, and in vivo xenograft models in nude mice. Additionally, we evaluated the therapeutic efficacy of the multi-kinase inhibitor Rottlerin both in vitro and in vivo.ResultsHigh PKCδ expression correlated with reduced 5-year progression-free survival and overall survival. Knockout of PKCδ repressed DLBCL cell proliferation, facilitated cell cycle arrest in the G2/M phase, induced apoptosis in vitro, and inhibited tumor growth in vivo, and enhanced sensitivity to rituximab and chemotherapeutics. Similarly, inhibition with the multi-kinase inhibitor Rottlerin also impaired tumor growth and showed combinatory efficacy with rituximab. RNA-seq revealed 2,988 differentially expressed genes enriched in AKT, MAPK, and NF-κB signaling pathways.DiscussionOur findings highlight PKCδ as a potential predictive biomarker and therapeutic target. However, due to the off-target effects of Rottlerin, the observed in vivo efficacy and synergistic effects of Rottlerin should be considered as preliminary pharmacological support for the concept of targeting PKCδ.